Art Decoration Design of Electrochemical Silicon Oxide Ceramic Sculpture Based on 3D Printing Technology - Jifeng Guo (Journal of Chemistry)
In order to solve the art decoration design of silicon oxide ceramic sculpture, a method for silicon oxide ceramic sculpture based on 3D printing technology is proposed. Firstly, the density of photosensitive resin premix before curing was measured by pycnometer method; the photosensitive resin was coated on tinplate and then put into a self-made UV curing box for curing. Secondly, the critical exposure and critical transmission depth of photosensitive resin without formula are calculated. Finally, the viscosity of ceramic slurry was measured by mixing S2 photosensitive resin formula with ceramic powder with different nano silica content. It is proved that the addition of nano silica powder can promote the decomposition of quartz glass and increase the sintering degree of the ceramic core. The primary sintering shrinkage of ceramic core gradually increases with the increase of nano silica content. In the length direction, the shrinkage increases from 3.33% to 5.61%; in the width direction, the shrinkage increases from 2.98% to 4.74%; and in the height direction, the shrinkage increases from 3.18% to 5.00%.